(untitled) (CIPEEX, 2022)
INTRODUCTION: THE FAMILY HEALTH STRATEGY IS THE GATEWAY OF THE USER TO THE UNIFIED HEALTH SYSTEM. IN THE FHS, ACTIONS ARE CARRIED OUT TO PROMOTE, PREVENT AND RECOVER THE HEALTH OF THE INDIVIDUAL AND THE COMMUNITY. THUS IN 2017 THE MINISTRY OF HEALTH REFORMULATES THE NATIONAL POLICY OF BASIC ATTENTION - PNAB TO OFFER A SERVICE OF QUALITY TO ITS POPULATION ATTACHED. OBJECTIVE: TO DESCRIBE USER SATISFACTION THROUGH CARE PROVIDED IN UNITS ESF, IN A MUNICIPALITY IN THE STATE OF GOIS. METHOD: DESCRIPTIVE STUDY OF A QUALITATIVE APPROACH. SAMPLE COMPOSED OF 30 PARTICIPANTS, RANDOMLY RECRUITED. DATA COLLECTION WAS PERFORMED IN JUNE AND JULY / 2017, THROUGH THE SEMI-STRUCTURED INTERVIEW, WHICH WERE LATER TRANSCRIBED AND ANALYZED BY THE BARDIN CONTENT ANALYSIS TECHNIQUE. RESULTS: THE AGE RANGE RANGED FROM 18 TO 73 YEARS. THE DURATION OF ESF USE WAS 2 TO 16 YEARS. TWO CENTRAL CATEGORIES ORIGINATED: "STRUCTURAL REALITY OF THE ESF" AND "EXPECTATION AND SATISFACTION OF THE ESF USER IN RELATION TO THE MULTIPROFESSIONAL TEAM". THE "STRUCTURAL REALITY OF ESF" WAS DIVIDED INTO TWO SUBCATEGORIES: "PHYSICAL STRUCTURE, EQUIPMENT AND FURNITURE" AND "ACCESS: GEOGRAPHICAL AND ORGANIZATIONAL BARRIER". ON THE PHYSICAL STRUCTURE THE PARTICIPANTS STATED THAT IT IS ADEQUATE, BUT COMPLAINED ABOUT: LACK OF COVERAGE AT THE CONCIERGE FOR SHELTER FROM THE SUN AND RAIN, ROOF REFORMS AND PRECARIOUSNESS OF THE WALLS. ON EQUIPMENT THEY POINTED OUT THE LACK OF HGT TAPES AND TONER, SPOILED INSTRUMENTS LIKE SCALES, PA APPARATUS AND COMPUTERS. AS FOR THE FURNITURE: SCARCE CHAIRS, BROKEN AND RUSTY. REGARDING ACCESS: ORGANIZATIONAL AND GEOGRAPHICAL BARRIERS IN THE GEOGRAPHICAL BARRIER, THE DIFFICULTIES WERE THE DISTANCE FROM THE RESIDENCE TO THE UNIT, IN SOME POINTS THERE ARE NO BUS LINES AND IN THE ORGANIZATIONAL BARRIER POINTED OUT: DIFFICULTY TO SCHEDULE APPOINTMENTS, INSUFFICIENT VACANCIES FOR EXAMS, SYSTEM OFF-LINE, LACK OF PROFESSIONALS. THE CATEGORY "EXPECTATION AND SATISFACTION OF THE ESF USER IN RELATION TO THE MULTIPROFESSIONAL TEAM" WAS DIVIDED INTO THREE SUBCATEGORIES: "TEAM AND INTERPERSONAL RELATIONSHIP", "HEALTH PROMOTION AND PROMOTION" AND "EXPECTATIONS FOR IMPROVEMENT". PROFESSIONALS WHO HAVE SOLVED THE MOST PROBLEMS: NURSES AND NURSING TECHNICIANS, AND TO A LESSER EXTENT THE SECRETARIES, HEALTH AGENTS AND THE DOCTOR. WHEN THEY DO NOT SOLVE THE PROBLEMS THE TEAM OFFERS GUIDANCE AND PERFORMS THE REFERRAL FOR CALLS IN OTHER PLACES. THE INTERPERSONAL RELATIONSHIP WITH THE TEAM WAS CLASSIFIED AS VERY GOOD, HIGHLIGHTING EDUCATION, AVAILABILITY AND CORDIALITY, ESPECIALLY WITH NURSES. THE PREVENTION AND HEALTH PROMOTION ACTIVITIES CARRIED OUT AT THE FHS ARE: HIKING, MAN’S DAY, CHILDREN’S WEIGH-IN, GYMNASTICS, HYPERDIA AND DAY OF THE PREGNANT WOMAN, BUT THERE IS NO ADHERENCE ON THE PART OF THE PARTICIPANTS. EXPECTATIONS FOR IMPROVEMENTS WERE: NO LACK OF MEDICATION, GLOVES, GAUZES AND TONER TO PRINT SCHEDULED APPOINTMENTS AND THE OPERATION OF COMPUTERS AND SCALES. CONCLUSION: THE PRESENT STUDY IS EXPECTED TO PROVIDE DATA FOR PLANNING, IMPLEMENTATION OF ACTIONS AND DECISION-MAKING IN THE FIELD OF PUBLIC HEALTH AIMING TO INCREASE USER SATISFACTION AND INCREASE QUALITY OF CARE.